Does mandatory reporting legislation increase contact with child protection? – a legal doctrinal review and an analytical examination - Lil Tonmyr; Ben Mathews; Margot E. Shields; Wendy E. Hovdestad; Tracie O. Afifi (BMC Public Health, 2018)
Abstract Background Within Canadian provinces over the past half-century, legislation has been enacted to increase child protection organization (CPO) involvement in situations of child maltreatment (CM). This study had two objectives: 1) to document enactment dates of legislation for mandatory reporting of CM; 2) to examine reported CPO involvement among people reporting a CM history in relation to the timing of these legislative changes. Methods The history of mandatory reporting of CM was compiled using secondary sources and doctrinal legal review of provincial legislation. The 2012 Canadian Community Health Survey - Mental Health (CCHS-MH) with n = 18,561 was analyzed using birth cohorts to assess associations between the timing of legislation enactment and contact with CPO. Results All Canadian provinces currently have mandatory reporting of physical and sexual abuse; 8 out of 10 provinces have mandatory reporting for children’s exposure to intimate partner violence. Increases in reporting CM to CPOs paralleled these laws’ enactment, particularly for severe and frequent CM. Conclusions These findings show that mandatory reporting laws increase reporting contact with CPO, particularly for severe and frequent CM. Whether they have had the intended effect of improving children’s lives remains an important, unanswered question.